2020
DOI: 10.1039/c9mh00500e
|View full text |Cite
|
Sign up to set email alerts
|

It's a trap! On the nature of localised states and charge trapping in lead halide perovskites

Abstract: The recent surge of scientific interest for lead halide perovskite semiconductors and optoelectronic devices has seen a mix of materials science sub-fields converge on the same “magical” crystal structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
366
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 411 publications
(384 citation statements)
references
References 159 publications
(199 reference statements)
15
366
2
1
Order By: Relevance
“…[ 40 ] This again emphasizes our previous discussion earlier that S doping can passivate defect states by bonding Pb cations in a way to prevent the formation of undercoordinated Pb or I vacancies. [ 41 ] The reduction of defect states also benefits from improved perovskite film quality with S–NiO. Less defect‐induced charge recombination occurred during hole transport and is consistent with our studies on PV devices.…”
Section: Resultssupporting
confidence: 88%
“…[ 40 ] This again emphasizes our previous discussion earlier that S doping can passivate defect states by bonding Pb cations in a way to prevent the formation of undercoordinated Pb or I vacancies. [ 41 ] The reduction of defect states also benefits from improved perovskite film quality with S–NiO. Less defect‐induced charge recombination occurred during hole transport and is consistent with our studies on PV devices.…”
Section: Resultssupporting
confidence: 88%
“…Moreover, by experiments and simulations, it has been shown that Pb off‐centering and tilting angle affect the MAPbI 3 bandgap; namely, an increase of the distortion of the structure brings to a reduction of the energy of the valence band due to the reduction of the (unusual) antibonding overlap between Pb 6s and I 5p atomic orbitals. Indeed, the benign nature of point defects in MHPs has been attributed to the chemical character of the valence band minimum and conduction band maximum orbitals . The above observations bring us to the conclusion that structural distortions induced by GBs might affect the energetics of point defects in the bulk of crystalline grains.…”
Section: Resultsmentioning
confidence: 99%
“…It has been established that the stability (under ambient/inert, dark/ light, thermal/room-temperature conditions) of the perovskite layer can be signicantly enhanced through composition engineering of the cation and anion elements, as well as through processing additives, antisolvent engineering and defect management. 99 For example, it has recently been demonstrated that triplehalide tailored MAPbI 2Àx BrCl x PPV devices can sustain over 95% of their initial efficiency under continuous light soaking under 1000 lx FL light for over 2000 h, 51 while MAPbI 3 and MAPbI 2 Br reference devices undergo signicant degradation. This is due to the key role of the small Cl À ions in causing the shrinkage in the perovskite crystal lattice and further retarding ion migration and halide segregation.…”
Section: Stability Of Low Light Opvsmentioning
confidence: 99%